Frequência de estro em fêmeas ovinas Santa Inês, Texel e Ile de France no noroeste do Paraná e desempenho de cordeiros 1/2 Dorper Santa Inês abatidos em três diferentes pesos - Lourenço, Fábio José (2009)
Two experiments were carried out, being the first to observe the frequency of estrus in ewe. There were used Santa Inês ewes (n = 16), Texel (n = 16) and Ile de France (n = 15) between July 2005 and December 2006, fed with levels of 12% (PB12) and 16% of crude protein (PB16). The data of solar radiation were recorded daily, and each two weeks there were collected blood samples for determination of progesterone plasma concentration of Santa Ines ewe. The females remained during the experimental period with a teaser impregnated with a mixture of sheep's tallow and powdered paint pigment, marking the females who accepted service, characterizing the onset of estrus. There were observed higher frequency of estrus expression in fortnights of less photoperiod, showing the influence of this factor on the reproductive activity of the three races. Santa Inês ewes did not express estrus during the first half of November and throughout the month of December 2005 and the last half of December 2006. Estrus was not observed for any of the three races in October 2006, the period coinciding with the increase in photoperiod. Statistical analysis revealed the existence of differences between races within the PB12 treatment, showing that Santa Inês and Ile de France ewes did not differ (P>0.05) among themselves for express estrus and both had higher probability (P<0.05) than Texel. When assessing the effect of treatments PB12 and PB16 on each race alone, it was found that levels of 12% and 16% of crude protein did not alter the probability of estrous expression in any of the breeds studied. The determination of progesterone plasma concentration of Santa Ines ewes, during spring of the years 2005 and 2006, indicated differences (P <0.05) between treatments PB12 (0.68 ng / mL) and PB16 (1.28 ng / mL) and between the years 2005 (0.39 ng / mL) and 2006 (1.47 ng / mL). The low values observed, particularly in 2005, showed the existence of anestrous periods of Santa Ines ewes. In the second experiment, there were evaluated the effect of slaughter weight on performance and carcass quantitative characteristics of 24 lambs Dorper ½ Santa Inês. The animals were finished in feedlot and weighed every week, until the slaughter weight, defined by different treatments being P28 (28 kg), P32 (32 kg) and P6 (36 kg). Intact males were slaughtered with age (109.27 days) lower (P <0.05) than females (118.41 days). No differences were found (P> 0.05) for daily weight gain and for the slaughter weight, type of birth or gender. The age at slaughter, weight gain and number of days at termination showed differences between groups for slaughter weight. The cost of the ending was different among all treatments evaluated, being R$ 20.64, R$ 24.69 and R $ 27.28 for P28, P32 and P36, respectively. The real and commercial yield of carcass did not differ (P> 0.05) in any of the factors evaluated. The index of carcass compactness was different between all treatments (P28: 0.2014; P32: 0.2209, and P36: 0.2481 kg cm-1), no difference were found in the index of leg compactness P28: 0.5002; P32: 0.4758, and P36: 0.4967). The loin area increased (P <0.05) due to the higher live weight at slaughter (P28: 13.99, P32: 15.48, and P36: 16.92 cm2) observing similar values for males (15.31 cm2) and females (15.60 cm2). Females showed higher values for larger and smaller fat thicknesses (4.23 and 2.75 mm) compared to males (2.73 and 1.8 mm). Only the highest fat thickness differed (P <0.05) between treatments, the P36 (4.55 mm) differed from P28 (2.83 mm) and P32 (3.11 mm). Regarding the proportion of muscle:fat:bone, there were observed values of 56.31:32.4:11.28, emphasizing the high value found for the fat proportion. The cuts weights varied only according to the treatment, a fact expected due to the increased of body mass of lambs with higher live weight at slaughter, no changes are observed from birth type or sex. The delivery of performance and carcass characteristics similar between treatments show that the effect of slaughter weight has an impact, mainly in the cost of termination, without changing significantly the final product, so it is recommended the lambs slaughter with 28 kg of weight.